The new Jim Crow : mass incarceration in the age of colorblindness - Alexander, Michelle; West, Cornel (New York : New Press, 2012)
This work argues that the War on Drugs and policies that deny convicted felons equal access to employment, housing, education, and public benefits create a permanent under caste based largely on race. As the United States celebrates the nation's "triumph over race" with the election of Barack Obama, the majority of young black men in major American cities are locked behind bars or have been labeled felons for life. Although Jim Crow laws have been wiped off the books, an astounding percentage of the African American community remains trapped in a subordinate status - much like their grandparents before them. In this incisive critique, former litigator-turned-legal-scholar Michelle Alexander provocatively argues that we have not ended racial caste in America: we have simply redesigned it. Alexander shows that, by targeting black men and decimating communities of color, the U.S. criminal justice system functions as a contemporary system of racial control, even as it formally adheres to the principle of color blindness. The New Jim Crow challenges the civil rights community - and all of us - to place mass incarceration at the forefront of a new movement for racial justice in America.
The rebirth of caste -- The lockdown -- The color of justice -- The cruel hand -- The new Jim Crow -- The fire this time.
Includes bibliographical references (pages 263-296) and index.
ENH
Trim Education
Keywords: Discrimination in criminal justice administration -- United States; Criminal justice, Administration of -- United States; African American prisoners -- United States; African American men -- Social conditions; Race discrimination -- United States; English language; African American men -- Social conditions; African American prisoners; Criminal justice, Administration of; Discrimination in criminal justice administration; Race discrimination; Race relations; Administration of criminal justice -- United States; African Americans -- United States; Prisoners -- United States; Race discrimination -- United States; United States -- Race relations; United States; United States -- Race relations